Microwave non‐destructive testing of active frequency selective surface embedded tunable radar absorber. Issue 19 (21st July 2020) - Sharma, A.; Panwar, R.; Khanna, R.
Abstract : The development and performance evaluation of a thin, broadband, and tunable radar wave absorber with reduced complexity is a strenuous task. This Letter reports the design, fabrication, and non‐destructive measurement of an active frequency selective surface (FSS) embedded tunable radar absorber. The proposed absorber design consists of periodically patterned, PIN diode mounted‐active transmissive/reflective FSS with a straightforward bias network. The tunable absorption characteristics are obtained over a wide frequency range by controlling the bias voltage of PIN diodes. The features of the proposed tunable absorber are demonstrated through non‐destructive free space, microwave measurement of a fabricated prototype. The measurement results show the achievement of a remarkable bandwidth of 3.0 GHz, which enables dynamic control of the absorption characteristics ranging from 8.2 to 12.4 GHz. Such an approach paves the way toward the realisation of smart materials and structures for electromagnetic wave manipulation.